ANALISIS PENENTUAN NISBAH BAGI HASIL TERHADAP PEMBIAYAAN MUDHARABAH DI PT. BPRS AL-FALAH BANYUASIN PALEMBANG - Erika Nurfitria; Meriyati Meriyati (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2018)
The focus of the research examined in this final project is the analysis of the determination of the profit sharing ratio of mudharabah financing at PT. BPRS Al-Falah Banyuasin Palembang. In this study, the authors used qualitative research, which describes the data obtained from the field regarding the research problems above. And answering the above problems, this study uses a qualitative descriptive method which is intended to describe or summarize various conditions, situations or women as they were when the research was carried out, namely summarizing the data on the analysis of the determination of the profit sharing ratio of mudharabah financing at PT. BPRS Al-Falah Banyuasin Palembang. Data collection techniques in this research using interviews (interviews), observation, and the library study method. This research implies that the analysis of the determination of the profit sharing ratio of mudharabah financing at PT. BPRS Al-Falah Banyuasin Palembang, namely: The Banyusin Palembang Al-Falah Sharia Financing Bank does not easily provide loans to customers. This is because the bank does not want the activities to be borne by the bank. In mudharabah financing, the amount of profit is determined based on a mutual agreement between the bank and the customer called profit sharing.